2017
DOI: 10.1055/s-0037-1601577
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cortical Comminution and Intra-articular Involvement in Distal Radius Fractures on Clinical Outcome: A Prospective Multicenter Study

Abstract: The purpose of this prospective multicenter study was to test the predictive value of cortical comminution and intra-articular involvement on function and quality of life in distal radius fractures (DRFs) using the Buttazzoni's classification system. We studied 406 patients between skeletal maturity and 74 years of age with DRF. Fractures with acceptable radiographic alignment were immobilized with a cast. Fractures with nonacceptable radiographic alignment underwent closed reduction and 4 to 6 weeks cast immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Postoperative pain is common in DRF patients even after surgical treatment [17]. The irregular articular surface has been demonstrated to be the main reason to increase the risk of traumatic osteoarthritis and to cause unsatisfactory function recovery [18][19][20], and if it is associated with postoperative pain remains unclear. To clarify this confusion, we made a comparison, and the results showed that patients with gaps or steps on the sigmoid notch have significantly more severe pain during forearm rotation at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is common in DRF patients even after surgical treatment [17]. The irregular articular surface has been demonstrated to be the main reason to increase the risk of traumatic osteoarthritis and to cause unsatisfactory function recovery [18][19][20], and if it is associated with postoperative pain remains unclear. To clarify this confusion, we made a comparison, and the results showed that patients with gaps or steps on the sigmoid notch have significantly more severe pain during forearm rotation at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is common in DRFs patients even after surgical treatment [17]. Irregular articular surface has been demonstrated to be the main reason to increase the risk of traumatic osteoarthritis and to cause unsatisfactory function recovery [18][19][20], and if it is associated with postoperative pain remains unclear. To clarify this confusion, we made a comparison, and the results showed that patients with gaps or steps on sigmoid notch have signi cant more severe pain during forearm rotation at the one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical examples of each subgroup are depicted in Fig 3 . 1. Volar comminution, with comminution defined as a free-floating piece of cortex > 3 mm [32].…”
Section: Plos Onementioning
confidence: 99%
“…4. Simultaneous presence of dorsal comminution (a free-floating piece of cortex > 3 mm [32]), severe initial displacement (dorsal angulation > 30˚, radial inclination < 10˚, or ulnar variance > 3 mm), and clinical suspicion of physiological osteopenia/osteoporosis � .…”
Section: Plos Onementioning
confidence: 99%